Association of Epicardial Fat Volume With Increased Risk of Obstructive Coronary Artery Disease in Chinese Patients With Suspected Coronary Artery Disease - Wenji Yu; Bao Liu; Feifei Zhang; Jianfeng Wang; Xiaoliang Shao; Xiaoyu Yang; Yunmei Shi; Bing Wang; Yiduo Xu; Yuetao Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Epicardial adipose tissue may be associated with the pathogenesis of coronary artery disease (CAD), but its effect on obstructive CAD risk is uncertain. Therefore, we aimed to examine the relationship between epicardial adipose tissue and obstructive CAD in Chinese patients with suspected CAD. Methods and Results The present study enrolled 194 consecutive inpatients with suspected CAD who underwent both noncontrast computed tomography and coronary angiography. We measured epicardial fat volume (EFV) and evaluated its association with obstructive CAD, which was defined as coronary stenosis severity ≥70%. Overall, 44.3% patients had obstructive CAD and tend to have higher EFV. Age, body mass index, triglycerides, incidence of hypertension, and hyperlipidemia were higher across tertiles of EFV (P for trend <0.05). In univariate regression analysis, a per‐SD increase in EFV was independently associated with obstructive CAD (odds ratio [OR], 2.31; 95% CI, 1.61–3.32; P<0.001). Consistent with these findings, EFV was still significantly related to obstructive CAD as continuous variable after adjustment for all traditional risk factors and coronary artery calcium (OR per SD, 2.82; 95% CI, 1.68–4.74; P<0.001). Generalized additive model indicated that EFV was linearly associated with risk of obstructive CAD. E‐value analysis suggested robustness to unmeasured confounding. Conclusions Our results suggested that in Chinese patients with suspected CAD, EFV was significantly and positively associated with the risk of obstructive CAD, independent of traditional risk factors and coronary artery calcium.